2010
DOI: 10.1021/jm100452c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthetic Peptides Belonging to E2 Envelope Protein of GB Virus C on Human Immunodeficiency Virus Type 1 Infection

Abstract: The use of synthetic peptides as HIV-1 inhibitors has been subject to research over recent years. Although the initial therapeutic attempts focused on HIV-coded enzymes, structural HIV proteins and, more specifically, the mechanisms that the virus uses to infect and replicate are now also considered therapeutic targets. The interest for viral fusion and entry inhibitors is growing significantly, given that they are applicable in combined therapies or when resistance to other antiretroviral drugs is seen and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…We cannot exclude the possibility that a three-dimensional protein structure within the native GBV-C E2 protein is important for the E2-mediated HIV-1 entry inhibition that might not be represented by a single peptide. Notably, Herrera et al could identify several regions within the GBV-C E2 protein that are supposed to interact with the fusion peptide of HIV-1 and thereby mediate antiretroviral activity in HIV-1 replication assays (11). In our study we screened for antiretroviral activity of peptides that exclusively represent the GBV-C E2 protein without the transmembrane anchor (aa 1 to 340) in a therapeutically relevant concentration (10 M).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We cannot exclude the possibility that a three-dimensional protein structure within the native GBV-C E2 protein is important for the E2-mediated HIV-1 entry inhibition that might not be represented by a single peptide. Notably, Herrera et al could identify several regions within the GBV-C E2 protein that are supposed to interact with the fusion peptide of HIV-1 and thereby mediate antiretroviral activity in HIV-1 replication assays (11). In our study we screened for antiretroviral activity of peptides that exclusively represent the GBV-C E2 protein without the transmembrane anchor (aa 1 to 340) in a therapeutically relevant concentration (10 M).…”
Section: Discussionmentioning
confidence: 99%
“…Haro and coworkers (10) could also demonstrate in biophysical assays that the peptide from amino acids 269 to 286 interacts with the fusion peptide of HIV-1 gp41. Latest results suggested that a broad range of E2-derived peptides interact with the gp41 fusion peptide and that the identified peptides were able to mediate HIV-1 inhibition in vitro (11). In the present study, we tested a panel of E2-derived peptides regarding their HIV-inhibitory capacity in various replication assays.…”
Section: Gb Virus C (Gbv-c) a Positive-strand Rna Virus Of The Flavimentioning
confidence: 95%
“…Recently, we described certain E2 GBV-C domains that interfered with the HIV-1 fusion peptide (FP)-vesicle interaction, decreased cellular membrane fusion, and interfered with HIV-1 infectivity in a dose-dependent manner. [8] The interaction of certain GBV-C peptide sequences of the E1 envelope protein, obtained by solid-phase peptide synthesis (SPPS), with the HIV-1 fusion peptide has been determined through the use of several biophysical techniques, such as isothermal titration calorimetry, confocal microscopy, binding assays, and fluorescence studies. Results have shown that five peptide sequences corresponding to the envelope protein E1 of GBV-C [NCCAPEDIGFCLEGGCLV (P7), APEDIGFCLEGGCLVALG (P8), FCLEGGCLVALGCTICTD (P10), QAGLAVRPGKSAAQLVGE (P18), and AQLVGELGSLYGPLSVSA (P22)] were capable of interfering with the HIV-1 FP-vesicle interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This includes an inverse relationship between GBV-C and HIV-1 RNA levels as well as an increase in GBV-C RNA levels in those starting potent antiretroviral therapy [ 20 ]. These observations argue for a causal virus-virus interaction which is supported by in vitro evidence for an attenuating effect of GBV-C on HIV replication [ [21][22][23][24]. Despite that, some authors still argue that the observation only indicates an epiphenomenon [ 25 ].…”
Section: Discussionmentioning
confidence: 99%